Fungal mobile mass on echocardiogram: native mitral valve Aspergillus fumigatus endocarditis. (8th December 2016) - Rofaiel, Rymon; Turkistani, Yosra; McCarty, David; Hosseini-Moghaddam, Seyed M
Abstract : The most common type of infective endocarditis is bacterial endocarditis. However, fungal infections have been seen more frequently, mostly in the immunocompromised population. We report a case of invasive Aspergillus fumigatus native mitral valve endocarditis. The patient received appropriate empiric antifungal treatment with a combination of liposomal amphotericin B and flucytosine, associated with surgical debridement, valve replacement and chordae tendineae repair. Despite receiving the standard treatment of Aspergillus endocarditis, and susceptibility of the microorganism to the antifungal regimen, the patient, unexpectedly, developed early-onset septic emboli. It is surprising to see that the patient had developed such complications early, despite attempts to eliminate the source of infection with surgical intervention.